ANALISIS TOKOH DAN PENOKOHAN PADA DRAMA RT NOL RW NOL KARYA IWAN SIMATUPANG - novia indrawan (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
The study, entitled the analysis of figures and characterizations in the drama "RT Nol RW Nol" by Iwan Simatupang, was motivated by the emergence of social criticism and conditions of marginalized society. This study aims to analyze the character and characterizations. The author concludes that the lives of small people, the homeless in the city, are not as bad as one might imagine. The method used is descriptive qualitative analysis. Data retrieval is done by reading, analyzing, and marking texts or sentences that belong to the characters and characterizations are done so that the characters in the drama are easy and characterizations are assessed and applied in the social life of the reader, with this research, the reader can implement in his social life don't give up easily, be patient, be generous and be people who know how to respect others. Like other community members, that they are citizens who are equally entitled to obtain their rights and dignity as citizens who are respected and recognized as well. The results of this research is there is social imbalance that occurs various conflicts caused by something that has an impact on social life. writer presents various characters in each character,and has succeeded in conveying what is happening in real life.